We have that
y = 2x²<span> + 2
step 1
</span><span>exchange the value of x for y and the value of y for x
</span>y = 2x² + 2------> x=2y²+2
step 2
clear y variable
x=2y²+2----> 2y²=x-2----> y²=[(x-2)/2]-----> y=(+/-)√[(x-2)/2]
step 3
the inverse is
f(x)-1=(+/-)√[(x-2)/2]
2238 - 300 = 1938 ft is your answer
For this case we have a function of the form:
y = A * (b) ^ t
Where,
A: initial amount
b: growth rate
t: time
Substituting values we have:
y = 1000 * (3) ^ ((1/8) * t)
For 24 years we have:
y = 1000 * (3) ^ ((1/8) * 24)
y = 27000
Answer:
D) 27,000; exponential
Answer:
6/16
Step-by-step explanation:
To get 16ths multiply both the top and bottom by 2
3*2=6
8*2=16
6/16ths =0.375
3/8ths=0.375
Answer:
D.The multiplicative identity
Step-by-step explanation:
3/4 x N and which N=1 you multiply them both and should get the same answer